2010
DOI: 10.4103/1817-1737.58958
|View full text |Cite
|
Sign up to set email alerts
|

Association and symptom characteristics of irritable bowel syndrome among bronchial asthma patients in Kuwait

Abstract: CONTEXT:Excess prevalence of irritable bowel syndrome in asthma has been reported, suggesting a link between these two conditions.AIMS:To investigate the association between irritable bowel syndrome (IBS) and asthma, and explore the symptoms of IBS among asthma patients in Kuwait.SETTINGS AND DESIGN:Case control study.METHODS:In a tertiary center, for allergy and asthma, 138 patients aged 20-65 years, with asthma, diagnosed clinically and by spirometry, were compared with 145 healthy, non-asthmatic controls ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
1
16
1
1
Order By: Relevance
“…Only those with persistent asthma were at an increased risk for IBS while the prevalence in those with mild asthma was similar to those without asthma. Previous studies already reported the association between asthma and IBS with an OR ranging from 1.3 to 5.0 . An association between IBS and severity of asthma has not been previously documented.…”
Section: Discussionmentioning
confidence: 92%
“…Only those with persistent asthma were at an increased risk for IBS while the prevalence in those with mild asthma was similar to those without asthma. Previous studies already reported the association between asthma and IBS with an OR ranging from 1.3 to 5.0 . An association between IBS and severity of asthma has not been previously documented.…”
Section: Discussionmentioning
confidence: 92%
“…found a similar pattern for IBS prevalence in asthmatics that was not apparently due to asthma therapy, although another study has shown an increased risk of IBS in asthma patients alongside a decreased risk for IBS in oral steroid users . Their findings were replicated by Panicker et al . who reported an OR for IBS of almost three in an allergy out‐patient sample in Kuwait and Hunskar et al .…”
Section: Introductionmentioning
confidence: 73%
“…There have been several reports of increased prevalence of IBS among atopic patients, especially patients with asthma. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] In a large primary care study of general practitioner diagnosed IBS, the odds ratio for IBS among asthma patients was 2-fold that of controls. 47 Tobin et al 33 reported increased mucosal mast cells in a group of IBS patients with concurrent atopic disease.…”
Section: Discussionmentioning
confidence: 99%